Turkey Economic Monitor February 2022 : Sailing Against the Tide (Washington, DC: World Bank, 2022)
Turkey’s economic performance has been a tale of two economies, overall high growth, matched by a deterioration in macro-financial conditions. Good progress in vaccination rollouts allowed Turkey to reopen gradually in 2021 despite a continued rise in Coronavirus (COVID-19) cases. Real economic activity remained strong, driven by strong broad-based export growth and domestic demand. Exports of goods reached record high levels in 2021 supported by buoyant external demand, improved price competitiveness and demand shifts to Turkey due to rising shipping costs. Turkey’s GDP grew by 22 percent year-on-year in 2021Q2–the second highest among G-20 countries–and 7.4 percent in 2021Q3. Strong goods and services export performance helped current account deficit to narrow significantly. Robust economic activity led to strong revenue growth and supported fiscal balances. The labor market saw a good recovery in 2021 and employment levels surpassed pre-pandemic levels, supported by buoyant economic activity. The regional inequalities of the COVID-19 shock manifested in larger impacts for women from Eastern regions, widening pre-existing gender gaps. The authorities began to cut interest rates in September, by 500 basis points by the end of 2021, despite rising inflation and inflation expectations. This has exacerbated macro-financial conditions and impacted investor confidence - causing financial market turbulence, large deprecation of the Lira, higher inflation, and increased dollarization. The Lira has been the most depreciating currency among emerging market economies this year. The large depreciation of the Lira coupled with rising international prices caused inflation to increase to its highest rate since the August 2018 shock.